IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG/JASA PEMERINTAH - ., Sularno (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
The phenomenon that made into the object of research is the implementation of the procurement of goods/services of government in Karimun. The research objective was to discuss the implementation of the procurement of goods/ services; discusses the factors that determine the effectiveness, efficiency and accountability in the implementation of the procurement of goods/services; and obtaining the right policy implementation model for conducting procurement of government goods/services. The study used a qualitative approach. Determination informant as much as 7 informant research study using purposive sampling technique. Secondary data collection using literature study and study documents. Primary data collection using interviews and observation techniques. The data analysis using descriptive analysis with triangulation approach. Results of the study are the following, Implementation of the procurement of goods/services in Karimun Regency Government is implementing Karimun Regent Regulation Number 31 Year 2012 on the Establishment of Procurement Services Unit Goods/Services Regional Governments Karimun. Implementation of procurement policy in question is an activity to obtain goods/services by SKPD that the process starts from planning until completion of all activities need to obtain goods/services. The procurement of goods/services are guided by the Presidential Decree Number 54 Year 2010 concerning Procurement of Government Goods/Services as well as regulation changes, the last Presidential Decree Number 172 Year 2014 on the Amendment to the three Presidential Decree Number 54 of 2010. The implementation of the procurement of goods/services of government in Karimun not optimal because there are still weaknesses in communication management procurement of goods/services. The factors that determine the effectiveness, efficiency and accountability in the procurement of government goods/services in Karimun is communication, resources, disposition apparatus attitudes and bureaucratic structure. Among the four factors, the communication in the process of implementation of the policy is a factor that most determines the effectiveness, efficiency and accountability in the procurement of government goods / services in Karimun. Keywords: Policy Implementation, Government, Goods /Services Procurement Â